Guidance and Counseling Program Management Strategy in Overcoming Student Problems at SMAN 1 Galis Pamekasan - Dewi Fuji Astutik (Penerbit Presisi Pustaka, 2026)
This study aims to examine the guidance and counseling program management strategies for addressing student problems at SMAN 1 Galis Pamekasan. The diverse range of student problems, including personal, social, learning, and career, requires systematic management through well-managed guidance and counseling services. This study employed a qualitative method with a library research approach, reviewing various books, journals, and scientific literature relevant to the research topic. The results indicate that effective guidance and counseling program management includes systematic program planning, the implementation of diverse counseling services, and ongoing program evaluation. Furthermore, the role of guidance and counseling teachers is crucial in providing services such as individual counseling, group counseling, and information services to help students address their problems. With appropriate management strategies, guidance and counseling services can make a significant contribution to supporting optimal student development.